Sdgs Compas of Pupuk Indonesia Holding Company: Analysing the Performance of Sustainability Reports - Sukoharsono, Eko Ganis (Accounting Department,, 2023)
Purpose: This study aims to analyze the performance of Pupuk Indonesia's Sustainability Report in relation to its contribution to the Sustainable Development Goals (SDGs). Specifically, it examines the suitability of the company's report disclosures based on the GRI Standards to demonstrate its SDG contributions. Method: The study employs a postmodernist approach, utilizing explorative dialogue as its primary methodology. Data was collected from Pupuk Indonesia's official sustainability reports published between 2019 and 2021. These reports were then analyzed through a constructed dialogue between an